Finland reforms the income basis for calculating pension insurance contributions for the self-employed - Olli Kangas (European Commission, 2025)
The Finnish government will reform the income basis for calculating pension insurance contributions for the self-employed. Currently, the selfemployed themselves can decide the income they will insure. Oftentimes, they choose the lowest contribution category, which leads to low earnings-related pensions. Furthermore, income chosen for pension contribution purposes has ramifications for other income transfers as well. For example, sickness and family leave benefits are calculated on the basis of pension-giving income. The reform will be effective from 1 January 2023.